Sistem Informasi Pengumuman Program Studi Di Perguruan Tinggi X - Setiyadi, Angga; Budi Setiawan, Eko (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 8, No. 1 April 2017, 2017)
Information technology is the result of a human mind to develop ordinances or specific systems and use them to solve problems in life. Submission of information today is no longer through the print media, but will gradually shift to the use of digital electronic media. The announcement can be interpreted as a message delivered to every person who is the target destination or destination information. This study discusses the announcement of information systems that can replace conventional media announcements still. With this information system of this announcement makes any lecturer and secretariat in one program studi in College X no longer need to print and posting notices on board the information available, but may be digital by entering the announcement into the system to afterwards the announcement will be displayed on each screen television or monitor the spread and available in every area of ??the campus. This can make the process of delivering information to become more effective and efisien if compared to the print media.
Keywords: Sistem Informasi; Pengumuman; Media Informasi; Akademik; Perguruan Tinggi.